2020
DOI: 10.1101/2020.08.11.20172809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Federated Learning of Electronic Health Records Improves Mortality Prediction in Patients Hospitalized with COVID-19

Abstract: Machine learning (ML) models require large datasets which may be siloed across different healthcare institutions. Using federated learning, a ML technique that avoids locally aggregating raw clinical data across multiple institutions, we predict mortality within seven days in hospitalized COVID-19 patients. Patient data was collected from Electronic Health Records (EHRs) from five hospitals within the Mount Sinai Health System (MSHS). Logistic Regression with L1 regularization (LASSO) and Multilayer Perceptron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…It has been proposed as a method to facilitate multi-national collaboration while obviating data transfer. In the setting of the COVID-19 pandemic 10,11 FL was used to allow the retention of data sovereignty and the enforcement of local governance policies over data repositories. In medical imaging, recent studies 5,12 demonstrated that federated training of deep learning models on brain tumour segmentation or breast density classification performs on-par with local training and that it fosters the inclusion of data from more diverse sources, leading to improved generalization.…”
Section: Evidence From Prior Workmentioning
confidence: 99%
“…It has been proposed as a method to facilitate multi-national collaboration while obviating data transfer. In the setting of the COVID-19 pandemic 10,11 FL was used to allow the retention of data sovereignty and the enforcement of local governance policies over data repositories. In medical imaging, recent studies 5,12 demonstrated that federated training of deep learning models on brain tumour segmentation or breast density classification performs on-par with local training and that it fosters the inclusion of data from more diverse sources, leading to improved generalization.…”
Section: Evidence From Prior Workmentioning
confidence: 99%
“…Federated learning (FL) is an emerging realm of ML concerned with distributed, decentralized training that stores privacy-sensitive data only locally (for details see 65,66,67 ). It allows multiple parties to collaboratively train the same model without data sharing and could thus become key to foster collaborations between clinical and AI communities and overcome privacy concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis included three preprints exploring FL using CT 68 or CXR 69 data. A recent FL study on EHR from 5 hospitals was found to improve COVID-19 mortality prediction 70 . These efforts will hopefully increase reproducibility and make comparative studies more feasible, which will help the research community focus on the highest performing methods.…”
Section: Discussionmentioning
confidence: 99%
“…The authors chose FL due to its ability to rapidly launch centrally orchestrated experiments with improved traceability of data and assessment of algorithmic changes and impact 29 . FL has shown promise in recent medical imaging applications [30][31][32][33] , including COVID-19 analysis [34][35][36][37] , albeit with limited scale. Governance of data for FL is maintained locally, alleviating privacy concerns, with only model 'weights' or 'gradients' transferred between the client-sites and the federated server 38,39 .…”
Section: Main Textmentioning
confidence: 99%